Flower [videorecording (DVD)] - Winkler, Max, 1983-; Deutch, Zoey, 1994-; Hahn, Kathryn, 1974-; Heidecker, Tim, 1976- (Lions Gate Entertainment, 2018)
Rebellious, quick-witted Erica Vandross is a sassy seventeen-year-old living with her single mom Laurie and mom's new boyfriend, Bob. When Bob's son, Luke, moves in with the family after a stint in rehab, Erica finds her life overwhelmed. With Luke and her sidekicks, Kala and Claudine, in tow, Erica acts out by exposing a dark secret of high school teacher Will, with perilous results. Their teenage kicks become a catalyst for growing up in unexpected and unpredictable ways.